LAW ENFORCEMENT IN MANAGEMENT OF POLICE OPERATIONAL FUNDS IN THE RIAU REGIONAL POLICE - Elga Gilbert Orion Sinaga; Fahmi; M. Fadly Daeng Yusuf (JILPR Journal Indonesia Law and Policy Review, 2026)
This study aims to analyze law enforcement in the management of police operational funds at the Riau Regional Police (Polda Riau), to examine the obstacles encountered in law enforcement related to the management of police operational funds, and to analyze efforts to overcome those obstacles. The research employs a sociological legal research method. The findings indicate that the management of operational funds constitutes an integral part of state financial management and must be carried out in accordance with the principles of transparency, accountability, effectiveness, efficiency, and compliance with applicable laws and regulations. Every official entrusted with the authority to manage operational funds bears legal responsibility for the use of such funds. Where abuse of authority, manipulation of accountability reports, misuse of budget allocations, or other acts resulting in state financial losses occur, the responsible parties may be held criminally liable pursuant to the provisions of the Law on the Eradication of Corruption and other legislation governing state financial management. The study further reveals several obstacles to effective law enforcement, including the difficulty of proving the element of abuse of authority, the suboptimal performance of the internal supervisory system, limited competence of human resources in public financial management, the lengthy process required for investigative audits, and an organizational culture that has not fully encouraged the reporting of suspected irregularities. These obstacles make the evidentiary process more complex and may hinder the timely, accurate, and accountable resolution of legal cases. To address these challenges, the study proposes strengthening the role of the Regional Inspectorate for Supervision (Inspektorat Pengawasan Daerah) in internal oversight, enhancing the competence of financial management officials through education and professional training, optimizing coordination with audit institutions and law enforcement agencies, utilizing information technology in financial management and supervisory systems, fostering a culture of integrity within the police institution, and ensuring firm and consistent law enforcement against every misuse of operational funds. These measures are expected to promote transparent and accountable management of operational funds within the Riau Regional Police while preventing criminal acts that cause losses to state finances.